The Implementation of the Pancasila Student Profile Strengthening Project Policy at State Elementary School 2 of Sokaraja Tengah in 2023 - Abbyad Al Jadid (Political Sciences Program Study, 2026)
This study aims to examine the implementation of the Pancasila Student Profile Strengthening Project (P5) policy at SDN 2 Sokaraja Tengah. This research employs a qualitative descriptive method. Informants were selected using a purposive sampling technique. Data were collected through interviews, observations, and documentation. The study was conducted at SDN 2 Sokaraja Tengah. Data analysis followed the model proposed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the P5 policy at SDN 2 Sokaraja Tengah demonstrates effective communication, reflected in the clarity, transmission, and consistency of information. However, challenges remain in teachers’ understanding of P5 and in maintaining continuous communication with parents. In terms of resources, support is considered adequate, as reflected in the strong commitment of teachers; nevertheless, limitations persist in conceptual understanding of P5 and the availability of teaching modules. Funding for P5 activities is supported by BOS funds and parental contributions managed transparently, although limitations in facilities and infrastructure remain a constraint. Regarding disposition, policy implementers, particularly the school principal, exhibit strong commitment and supportive attitudes, fostering active collaboration despite existing challenges. The bureaucratic structure functions well, supported by clear and systematic Standard Operating Procedures (SOPs), although detailed understanding of SOPs is not yet evenly distributed among school members. This study contributes to the enrichment of educational policy studies, particularly by providing insights into the alignment between policy design at the political level and implementation capacity at the school level, which has often been overlooked in policy analysis.